2021
DOI: 10.1111/aji.13389
|View full text |Cite
|
Sign up to set email alerts
|

The impact of autoimmune systemic inflammation and associated medications on male reproductive health in patients with chronic rheumatological, dermatological, and gastroenterological diseases: A systematic review

Abstract: Autoimmune disorders currently affect 5%‐8% of the global population, characterized by an aberrant chronic inflammatory response to self‐antigens. The aim of this study was to systematically review the current available evidence investigating the impact of systemic autoimmune diseases and associated immunosuppressive treatment on fertility parameters of adult men. Clinical trials, observational studies, and case reports written in English and reporting semen analysis, evaluation of seminal oxidative stress, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
(138 reference statements)
0
11
0
7
Order By: Relevance
“…Reproductive tract inflammation and infections are causes of male infertility, most prominently bacterial infections, environmental causes and autoimmunity [66]. This may also include systemic autoimmune disease and chronic asymptomatic inflammation associated with obesity, metabolic syndrome and diabetes mellitus [67,68]. It is known that viral infections may negatively affect fertility, including adenovirus, herpes simplex virus, HIV, hepatitis B and C [63,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive tract inflammation and infections are causes of male infertility, most prominently bacterial infections, environmental causes and autoimmunity [66]. This may also include systemic autoimmune disease and chronic asymptomatic inflammation associated with obesity, metabolic syndrome and diabetes mellitus [67,68]. It is known that viral infections may negatively affect fertility, including adenovirus, herpes simplex virus, HIV, hepatitis B and C [63,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that systemic inflammation and certain andrological comorbidities frequently present in men with IA (i.e. hypogonadism or varicocele) [ 7 ] have been associated with abnormal sperm DNA and low sperm quality [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die Datenbasis zu möglichen Auswirkungen rheumatologischer Erkrankungen auf die reproduktive und sexuelle Gesundheit des Mannes ist insgesamt jedoch sehr begrenzt; für zahlreiche Therapiemodalitäten, insbesondere neuere Biologika, liegen noch keine entsprechenden Studien vor [12][13][14][15][16]. Die Beratung betroffener Patienten bzw.…”
Section: Zusammenfassungunclassified
“…Inhibitoren wie z. B. Etanercept oder Infliximab vor[12][13][14][15]. Bei Patienten mit Spondylitis ankylosans (radiografische axiale Spondylo arthritis) hatte die Behandlung mit TNF-Inhibitoren keine negativen Auswirkungen auf die Ejakulatqualität; in einigen Studien wurde eine Verbesserung der Spermien parameter unter Infliximab berichtet[14].…”
unclassified